Perancangan Keamanan Jaringan Komputer Pada Router Dengan Metode ACL Pada PT. Aruna Sinar Jaya Jakarta - Cahyo Candra Wijaya; Ade Surya Budiman (ZETROEM, 2023)
At PT. Aruna Sinar Jaya, the Internet network plays an important role in running the company's wheel. The problem is that some client computers that do not require an internet connection in their work still have access to the Internet, sometimes the Internet is overused that is not related to work. To solve the above problems, network security methods such as Access Control List (ACL) are needed to make Internet use in Aruna Sinar Jaya more controlled and efficient. In this case, the author recommends implementing ACL on Mikrotik routers using Winbox to restrict internet connections. Keywords: Access Control List, Microtic Router, Winbox.